Assessing the distribution of disease‐bearing rodents in human‐modified tropical landscapes. Issue 3 (4th April 2015) - Morand, Serge; Bordes, Frédéric; Blasdell, Kim; Pilosof, Shai; Cornu, Jean‐François; Chaisiri, Kittipong; Chaval, Yannick; Cosson, Jean‐François; Claude, Julien; Feyfant, Tristan; Herbreteau, Vincent; Dupuy, Stéphane; et al.
Summary We tested how habitat structure and fragmentation affect the spatial distribution of common murine rodents inhabiting human‐dominated landscapes in South‐East Asia. The spatial distribution patterns observed for each rodent species were then used to assess how changes in habitat structure may potentially affect the risk of several major rodent‐borne diseases. For this analysis, we used an extensive geo‐referenced data base containing details of rodents trapped from seven sites in Thailand, Cambodia and Lao PDR. We also developed land‐cover layers for each site. Results from published studies that screened for five major rodent‐borne pathogens in rodents were used to estimate how these pathogens would likely be impacted by these alterations in habitat structure and composition. Our results confirmed the specialist and/or synanthropic status of several rodent species, although the majority of species studied demonstrated some degree of low level of habitat specialization. Habitat diversity and its alteration (decreasing forest cover, increasing fragmentation, increasing urbanization) were found to favour the presence of synanthropic rodent species such as Rattus tanezumi, known to damage crops and host important rodent‐borne diseases. Synthesis and applications. The five major rodent‐borne pathogens were linked to ongoing changes in habitat structure. In particular, the presence of Bartonella spp. and hantaviruses seemed to be favoured in wooded landscapes affected by ongoing fragmentation and human encroachments. Rodents also pose significant problems for crop production in South‐East Asia. Our results showed that the structure of the landscape affects the likely presence of rodent species considered as agricultural pests. The patchy structure of a landscape can either enhance, such as B. indica, or decrease, such as B. savilei, the presence of rodents that may cause serious damage to crops.